Sulphation and Hydrolysis Improvements of Bioactivities, and Immuno-Modulatory Properties of Edible Amanita hemibapha Subspecies javanica (Corner and Bas) Mucilage Polysaccharide as a Potential in Personalized Functional Foods - Utoomporn Surayot; Sutee Wangtueai; Sangguan You; Charin Techapun; Yuthana Phimolsiripol; Noppol Leksawasdi; Warawut Krusong; Francisco J. Barba; Phisit Seesuriyachan (My University, 2021)
In this study, the mucilage polysaccharide (MP) from Amanita hemibapha subspecies javanica was prepared by hot water extraction and ethanol precipitation and then fractionated using anion-exchange chromatography equipped with a DEAE Sepharose fast flow column. The most immune-enhancing polysaccharide fraction 2 (MPF2) was subjected to a structural modification such as hydrolysis or over-sulphation. The sulphate and molecular weight (Mw) of over-sulphated (OS1-3) and hydrolysed (HS1-3) derivatives of MPF2 differed between 9.85% and 14.2% and 32.8 and 88.1 × 103 g/mol, respectively. Further, the immune-enhancing properties of MPF2 and its derivatives were tested on RAW264.7 and NK cells through various in vitro assays. Interestingly, a low molecular weight of HS1-3 significantly increased the nitric oxide (NO) production (p < 0.05) more than MPF2, indicating that Mw is a major factor in RAW264.7 cell stimulation. In addition, RAW264.7 cells produced various cytokines by up-regulating mRNA expression levels and the activation of nuclear factor kappa-B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways. On the other hand, OS1-3-treated natural killer (NK) cells induced cytotoxicity in HepG2 cells through the expression of IFN-γ, Grandzyme-B, perforin, NKp30, and FasL. These results demonstrated that sulphate derivatives play an important role in NK cell activation. Further, this study also explores how polysaccharide binds to RAW264.7 and NK cells. MPF2 and HS3 may activate RAW264.7 cells via binding to TLR4 receptors, and OS2 could be activated through the CR3 signalling pathways.
Keywords: Mucilage; Subspecies; Amanita; Polysaccharides and Plant Cell Walls